Allocation of 14C assimilated in late spring to tissue and biochemical stem components of cork oak (Quercus suber L.) over the seasons - Aguado, Pedro L.; Curt, M. Dolores; Pereira, Helena; Fernández, Jesús (Tree Physiology, 2012)
Carbon distribution in the stem of 2-year-old cork oak plants was studied by 14CO2 pulse labeling in late spring in order to trace the allocation of photoassimilates to tissue and biochemical stem components of cork oak. The fate of 14C photoassimilated carbon was followed during two periods: the first 72 h (short-term study) and the first 52 weeks (long-term study) after the 14CO2 photosynthetic assimilation. The results showed that 14C allocation to stem tissues was dependent on the time passed since photoassimilation and on the season of the year. In the first 3 h all 14C was found in the polar extractives. After 3 h, it started to be allocated to other stem fractions. In 1 day, 14C was allocated mostly to vascular cambium and, to a lesser extent, to primary phloem; no presence of 14C was recorded for the periderm. However, translocation of 14C to phellem was observed from 1 week after 14CO2 pulse labeling. The phellogen was not completely active in its entire circumference at labeling, unlike the vascular cambium; this was the tissue that accumulated most photoassimilated 14C at the earliest sampling. The fraction of leaf-assimilated 14C that was used by the stem peaked at 57% 1 week after 14CO2 plant exposure. The time lag between C photoassimilation and suberin accumulation was ∼8 h, but the most active period for suberin accumulation was between 3 and 7 days. Suberin, which represented only 1.77% of the stem weight, acted as a highly effective sink for the carbon photoassimilated in late spring since suberin specific radioactivity was much higher than for any other stem component as early as only 1 week after 14C plant labeling. This trend was maintained throughout the whole experiment. The examination of microautoradiographs taken over 1 year provided a new method for quantifying xylem growth. Using this approach it was found that there was more secondary xylem growth in late spring than in other times of the year, because the calculated average cell division time was much shorter.
10.1093/treephys/tps01210.1093/treephys/tps012
Keywords: C-14 labeled compounds; carbon assimilation; microautoradiography; Quercus suber; suberin

How Plants Cope with Water Stress in the Field? Photosynthesis and Growth - Chaves, M M; Pereira, J S; MAROCO, J; RODRIGUES, M L; RICARDO, C P P; OSÓRIO, M L; CARVALHO, I; Faria, T; PINHEIRO, C (Annals of Botany, 2002)
Plants are often subjected to periods of soil and atmospheric water deficit during their life cycle. The frequency of such phenomena is likely to increase in the future even outside today’s arid/semi‐arid regions. Plant responses to water scarcity are complex, involving deleterious and/or adaptive changes, and under field conditions these responses can be synergistically or antagonistically modified by the superimposition of other stresses. This complexity is illustrated using examples of woody and herbaceous species mostly from Mediterranean‐type ecosystems, with strategies ranging from drought‐avoidance, as in winter/spring annuals or in deep‐rooted perennials, to the stress resistance of sclerophylls. Differences among species that can be traced to different capacities for water acquisition, rather than to differences in metabolism at a given water status, are described. Changes in the root : shoot ratio or the temporary accumulation of reserves in the stem are accompanied by alterations in nitrogen and carbon metabolism, the fine regulation of which is still largely unknown. At the leaf level, the dissipation of excitation energy through processes other than photosynthetic C‐metabolism is an important defence mechanism under conditions of water stress and is accompanied by down‐regulation of photochemistry and, in the longer term, of carbon metabolism.
10.1093/aob/mcf105
Keywords: carbon assimilation; high temperature; Lupinus; photosynthesis; Quercus ilex; Quercus suber; stomatal functioning; Stress; Vitis vinifera; water-stress; xanthophyll cycle

How Plants Cope with Water Stress in the Field? Photosynthesis and Growth - Chaves, M. M.; Pereira, J. S.; MAROCO, J.; Rodrigues, M. L.; RICARDO, C. P. P.; OSÓRIO, M. L.; CARVALHO, I.; FARIA, T.; PINHEIRO, C. (Annals of Botany, 2002)
Plants are often subjected to periods of soil and atmospheric water deficit during their life cycle. The frequency of such phenomena is likely to increase in the future even outside today’s arid/semi‐arid regions. Plant responses to water scarcity are complex, involving deleterious and/or adaptive changes, and under field conditions these responses can be synergistically or antagonistically modified by the superimposition of other stresses. This complexity is illustrated using examples of woody and herbaceous species mostly from Mediterranean‐type ecosystems, with strategies ranging from drought‐avoidance, as in winter/spring annuals or in deep‐rooted perennials, to the stress resistance of sclerophylls. Differences among species that can be traced to different capacities for water acquisition, rather than to differences in metabolism at a given water status, are described. Changes in the root : shoot ratio or the temporary accumulation of reserves in the stem are accompanied by alterations in nitrogen and carbon metabolism, the fine regulation of which is still largely unknown. At the leaf level, the dissipation of excitation energy through processes other than photosynthetic C‐metabolism is an important defence mechanism under conditions of water stress and is accompanied by down‐regulation of photochemistry and, in the longer term, of carbon metabolism.
10.1093/aob/mcf10510.1093/aob/mcf105
Keywords: carbon assimilation; high temperature; Lupinus; photosynthesis; Quercus ilex; Quercus suber; stomatal functioning; Stress; Vitis vinifera; water-stress; xanthophyll cycle

Fluorescence Parameters Measured Concurrently with Net Photosynthesis to Investigate Chloroplastic CO2 Concentration in Leaves of Quercus ilex L. - Di Marco, Giorgio; Manes, Fausto; Tricoli, Domenico; Vitale, Elisabetta (Journal of Plant Physiology, 1990)
Summary The relationship between net carbon assimilation and non-photochemical quenching (qN) was studied in Q. ilex. In leaf discs, in saturating C02 at various irradiances, qN responded linearly in a 1:1 relationship to 1-A/Ap, which represents the proportion of light energy that is not used in photosynthesis. In calculating Ap, a measured, maximal quantum yield for CO2 fixation of 0.080 for 1-year-oldleaves and 0.085 for young leaveswas used. In attached leaves, under natural conditions, this 1: 1 relation was found when a quantum yield of 0.020 and 0.031 was adopted respectively. According to a model of leaf photosynthesis these quantum yields correspond to stromal CO2 concentrations of 90 and 120μLL L-1, in contrast to an average value of substomatal CO2 concentration of 280μLL L-1 found through gas exchange measurements. Similar results were obtained when the relative increase of fluorescence, observed after a saturating flash given during steady photosynthesis at different irradiances, was plotted against the quantum yield of CO2 fixation. The slope of this relation in attached leaves differed from the slope obtained in saturating CO2 in the leaf discs to such an extent as to indicate stromal CO2 concentrations slightly lower compared with the above values obtained by using qE. The marked difference between stromal and substomatal CO2 concentration could be explained by the highly sclerophyllous character of Q. ilex leaves.
Keywords: carbon assimilation; fluorescence; fluorescence quenching; quantum yield; Quercus ilex; stromal CO2